TOWERS: T‐One with Enhanced Robustness and Speed. Issue 1 (31st July 2015) - Eldeniz, Cihat; Finsterbusch, Jürgen; Lin, Weili; An, Hongyu
Abstract : Purpose: A new T1 mapping method is proposed that is accurate, rapid, and robust to motion. Considering these features, the method is dubbed "T‐One with Enhanced Robustness and Speed (TOWERS)." Methods: TOWERS is composed of inversion recovery (IR) and saturation recovery (SR) acquisitions. In the IR acquisitions, a slice reordering scheme is used to sample all slices in an efficient manner, whereas the SR acquisitions serve as references for motion estimation. Furthermore, as opposed to the usual way of running generalized autocalibrating partially parallel acquisitions (GRAPPA) calibration only once at the beginning, GRAPPA coefficients are updated in the middle and at the end, and are later used for retrospectively correcting for motion artifacts. Finally, sub‐voxel magnetization tracking is deployed to account for motion‐induced signal evolution changes. Results: Whole‐brain T1 mapping data with a spatial resolution of 1.56 × 1.56 × 2.00 mm can be collected within 2.5 min. TOWERS and the gold‐standard IR method agree well in phantom, while high reproducibility is achieved in vivo. High‐quality T1 maps in the presence of severe motion show the robustness of the method. Conclusion: The proposed method, TOWERS, is shown to be rapid, accurate, and robust. Multiple GRAPPA calibrations and sub‐voxel magnetization tracking make TOWERS unique. Magn Reson Med 76:118–126, 2016. © 2015 Wiley Periodicals, Inc.